2015
DOI: 10.1182/blood-2015-01-620781
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic repartition of monocyte subsets as a diagnostic signature of chronic myelomonocytic leukemia

Abstract: Key Points An increase in the classical monocyte subset to >94% of total monocytes discriminates CMML from other monocytoses with high specificity. This characteristic increase in classical monocytes disappears in CMML patients who respond to hypomethylating agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
236
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(258 citation statements)
references
References 52 publications
16
236
1
5
Order By: Relevance
“…[55][56][57][58][59] Pathologically, a recent study by Solary et al demonstrated that the characteristic monocytosis is, in fact, an expansion of classical monocytes with reduction of other nonclassical monocytic subtypes. 60 This phenotype was present across all patients studied and was capable of distinguishing CMML from other entities with benign causes of monocytosis. 60 Classical monocytes represent the inflammatory monocytic subset and are preferentially recruited to sites of tissue injury or infection via the CCR2-CCL2 axis, which is upregulated in CMML.…”
Section: Inflammatory and Cell Extrinsic Phenotypesmentioning
confidence: 81%
See 1 more Smart Citation
“…[55][56][57][58][59] Pathologically, a recent study by Solary et al demonstrated that the characteristic monocytosis is, in fact, an expansion of classical monocytes with reduction of other nonclassical monocytic subtypes. 60 This phenotype was present across all patients studied and was capable of distinguishing CMML from other entities with benign causes of monocytosis. 60 Classical monocytes represent the inflammatory monocytic subset and are preferentially recruited to sites of tissue injury or infection via the CCR2-CCL2 axis, which is upregulated in CMML.…”
Section: Inflammatory and Cell Extrinsic Phenotypesmentioning
confidence: 81%
“…60 This phenotype was present across all patients studied and was capable of distinguishing CMML from other entities with benign causes of monocytosis. 60 Classical monocytes represent the inflammatory monocytic subset and are preferentially recruited to sites of tissue injury or infection via the CCR2-CCL2 axis, which is upregulated in CMML. The association between classical monocytosis and CMML is so robust that this assay is now being validated as a diagnostic modality in CMML.…”
Section: Inflammatory and Cell Extrinsic Phenotypesmentioning
confidence: 81%
“…Researchers compared the population of monocytes among healthy bone marrow donors, patients with reactive monocytosis, another hematologic malignancy, and CMML patients, which demonstrate a characteristic increase in the fraction of CD14+/CD16− cells compared with the other samples [23].…”
Section: Classical Monocytes Cd14mentioning
confidence: 99%
“…Reactive monocytoses, e.g., caused by chronic infections or inflammation, are associated with expansion of intermediate (CD14+/CD16+) and non-classical (CD14−/CD16+) monocytes, whereas a proportion of 'classical' CD14+/ Monocytosis persistent for at least 3 months, with other causes excluded CD16− monocytes >94% predicts CMML with good accuracy ( Fig. 1) [25].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Recurrent oncogenes can be broadly stratified into four distinct families, with a certain degree of mutual exclusion [25] within each of these families (Fig. 2).…”
Section: Molecular Lesions and Pathogenesismentioning
confidence: 99%